The Effect of Free Cash Flow, Profitability, Firm Size, and Leverage on Earnings Management - Saputri, Karlina; Sri Rahayu; Widya Sari Wendry (Cita konsultindo, 2026)
This study aims to determine and examine the effect of free cash flow, profitability, firm size, and leverage on earnings management. Differences in interests between management and external parties create opportunities for management to manipulate earnings, which is known as earnings management. This research employs a quantitative approach with a sampling technique using the purposive sampling method. The results of this study indicate that free cash flow, profitability, firm size, and leverage simultaneously affect earnings management. Partially, profitability has a significant effect on earnings management. Meanwhile, free cash flow, firm size, and leverage do not have a significant effect on earnings management.